Our Festschrift for Allen: An Introduction and Conclusion - David Carson Berry (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
This essay offers the editor’s commentary on A Music-Theoretical Matrix: Essays in Honor of Allen Forte, a Festschrift serialized in five installments (2009–2013) in the online music-theory journal Gamut. The Festschrift consists of twenty-two articles by Forte’s former doctoral advisees, and three special features: a previously unpublished article by Forte on Gershwin songs, a collection of tributes and reminiscences from forty-two of his former advisees, and an annotated register of his publications and advisees. (The complete content of the Festschrift is given in an Appendix.) The essay provides general information about the Festschrift: how it originated, how it came to take its serialized form and title, and points of orientation for the reader with respect to its content. An epilogue offers a brief summation of the significance of the honoree, to both the contributors and the field at large. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).